A critical study of the internal security act 1960 in Malaysia with specific references to The United States of America patriot act 2001 / Hisyam Hedzril Nor Hashim ...[et al.] - Nor Hashim, Hisyam Hedzril; Shabaath Ali, Sharul; Burhan @ Jaohari, Nik Saiful Adli; Azhar, Ahmad Naqib (2009)
Since November 1960, 138 persons had been detained without trial under the Internal Security Act 1960 (ISA). For a long time, the discussion on the validity and reasonableness of the ISA was done by persons in legal profession only. As the time changes, people have access towards media such as blog and international news coverage which are difficult to be filtered by the government. It had changed the mind of the people towards the ISA. Certain people claim that the ISA is unconstitutional and violating the human right. Therefore, a critical study of the ISA in Malaysia had been conducted with reference to the United States of America Patriot Act 2001 to find the defect of the ISA and to compare the application of this security measure in Malaysia with USA. In this study, two interviews had been conducted using e-mail with noted person regarding to the ISA from each side of the government and the opposition parties. Besides, there are also references from books, journals, reports, articles as well as internet sources. This study which contains five chapters had focusing on the current issue regarding to the jurisdiction and scope of the ISA, violation of human right, powers of the minister and misuse of power by the authority. It had comes with a lot of findings and critical views which become the basis of the suggestion at the end this study.